Air-stable formamidinium/methylammonium mixed lead iodide perovskite integral microcrystals with low trap density and high photo-responsivity. Issue 6 (23rd January 2019) - Wu, Guangbao; Zhou, Jiyu; Meng, Rui; Xue, Baoda; Zhou, Huiqiong; Tang, Zhiyong; Zhang, Yuan
Abstract : Here based on integral microcrystals (IMC) of halide perovskites containing formamidinium (FA)/methylammonium (MA) mixed cations, we investigate the impact of the addition of MAPbBr3 on the stability and optoelectronic properties in FA-based IMC films. Abstract : Here based on integral microcrystal (IMC) thin films of halide perovskites containing formamidinium (FA)/methylammonium (MA) mixed cations, afforded by a facile approach combining an anti-solvent and inverse temperature crystallization, we investigate the impact of the addition of MAPbBr3 on the phase, thermal and environmental stabilities as well as the opto-electronic properties in FA-based IMC films. By single-crystal XRD, FA based IMCs have been found to possess a perfect cubic structure showing a slight lattice contraction compared to pristine FAPbI3 crystals. In conjunction with optical and electrical analyses, the essential role of the introduced MA and Br ions in stabilizing the black phase in FA-based IMCs has been clarified, which explains the observed enhancement of photoluminescence and reduced trap densities. We also achieve stable pure FAPbI3 crystals that do not exhibit a yellow-phase transition after one month in air. By utilizing (FAPbI3 )1− x (MAPbBr3 ) x IMCs as the photo-absorber, we realize highly photo-responsive photodiodes with a satisfactory stability in air and thermal stability upon heating. Of interest, the best photoresponsivity exceeding 300 A W −1 is achieved upon appropriate air-exposure, which is among the highest values reported for FA-based perovskite photodetectors. The air-modified optoelectronic behaviour can be related to the trap passivation through the surface physisorption of the environmental O2, leading to reduced trap densities and resultant harmful SRH recombination.